Pengaruh konsumsi suplemen ekstrak kulit manggis (Garcinia mangostana L.) terhadap inflamasi gingiva pada pasien ortodonti cekat (kajian jumlah leukosit cairan sulkus gingiva) - P. Prayitno; Anggy Natya Listyaningrum (Majalah Kedokteran Gigi Indonesia, 2017)
Effect of taking mangosteen peel extract (Garcinia mangostana L.) supplement on gingival inflammation in fixed orthodontic patients (A study of leukocyte count of gingival crevicular fluid). Patients with fixed orthodontic appliances have a high risk of gingival inflammation. Gingival inflammation is characterized by an increase in leukocyte count of gingival crevicular fluid resulting in proinflammatory cytokines that are capable of damaging the gingival tissue. Mangosteen peel (Garcinia mangostana L) contains xantone which has anti-inflammatory properties. The objective of this study was to determine the effect of consuming mangosteen peel extract (Garcinia mangostana L) supplement on gingival inflammation in patients with fixed orthodontic by studying the leukocyte counts of gingival crevicularuid. Twenty patients with fixed orthodontic appliances were divided into two groups: 10 subjects in the control group and 10 subjects in the treatment group. They were selected based on the following criteria: age 18-24 years, suffering from mild to moderate gingivitis, and using fixed orthodontic appliances in the final phase. The subjects in both groups underwent initial therapy in the form of scaling, then the subjects in the treatment group took 2 capsules of mangosteen peel extract supplements three times a day for seven days. The sampling of gingival crevicular fluid of both groups was taken on day 0 and 8 in the lower anterior region, that is 3 samples of gingival crevicular fluid per subject. Leukocytes were seen from the results of staining with Turk’s reagents through microscope with a magnification of 400 times. The average leukocyte counts were analyzed using Pair T-test and Independent Sample T-test. The results showed that taking mangosteen peel extract (Garcinia mangostana L) supplements has significant effect on the decrease in leukocyte counts of gingival crevicular fluids (p<0.05). The conclusion of this study is the consumption of mangosteen peel extract (Garcinia mangostana L) supplement signicantly influences the reduction of gingival inflammation in patients with fixed orthodontic appliances, evident from the decline in the leukocyte counts of gingival crevicular fluids. ABSTRAKPasien pemakai ortodonti cekat memiliki resiko tinggi mengalami inflamasi gingiva. Inflamasi gingiva ditandai dengan meningkatnya jumlah leukosit cairan sulkus gingiva yang menghasilkan sitokin proinflamasi yang mampu merusak jaringan gingiva. Kulit manggis (Garcinia mangostana L) mengandung xantone yang memiliki sifat antiinflamasi. Tujuan penelitian ini adalah untuk mengetahui pengaruh konsumsi suplemen ekstrak kulit manggis (Garcinia mangostanaL) terhadap inflamasi gingiva pada pasien ortodonti cekat dengan kajian jumlah leukosit pada cairan sulkus gingiva. Dua puluh pasien ortodonti cekat dibagi menjadi dua kelompok, 10 subjek pada kelompok kontrol dan 10 subjek pada kelompok perlakuan yang diseleksi berdasarkan kriteria: usia 18-24 tahun, menderita gingivitis ringan hingga sedang, dan menggunakan alat ortodonti cekat pada fase akhir. Subjek pada kedua kelompok dilakukan initial therapy berupa scaling, kemudian subjek pada kelompok perlakuan mengkonsumsi suplemen ekstrak kulit manggis 2 kapsul 3 kali sehari selama 7 hari. Pengambilan sampel cairan sulkus gingiva kedua kelompok dilakukan pada hari ke-0 dan ke-8 pada regio anterior bawah sebanyak 3 sampel cairan sulkus gingiva tiap subjek. Leukosit dilihat dari hasil pewarnaan reagen Turk melalui mikroskop dengan perbesaran 400 kali. Hasil rerata jumlah leukosit dianalisis menggunakan uji Pair T-test dan uji Independent Sample T-test. Hasil penelitian menunjukkan bahwa mengkonsumsi suplemen ekstrak kulit manggis (Garcinia mangostana L) berpengaruh terhadap penurunan jumlah leukosit  cairan sulkus  gingiva secara signifikan  (p < 0,05). Kesimpulan dari penelitian ini adalah konsumsi suplemen ekstrak kulit manggis (Garcinia mangostana L) berpengaruh secara signifikan terhadap penurunan inflamasi gingiva pada pasien ortodonti cekat dilihat dari penurunan jumlah leukosit cairan sulkus gingivanya.